1999
DOI: 10.1105/tpc.11.10.1827
|View full text |Cite
|
Sign up to set email alerts
|

Function Search in a Large Transcription Factor Gene Family in Arabidopsis: Assessing the Potential of Reverse Genetics to Identify Insertional Mutations in R2R3 MYB Genes

Abstract: More than 92 genes encoding MYB transcription factors of the R2R3 class have been described in Arabidopsis. The functions of a few members of this large gene family have been described, indicating important roles for R2R3 MYB transcription factors in the regulation of secondary metabolism, cell shape, and disease resistance, and in responses to growth regulators and stresses. For the majority of the genes in this family, however, little functional information is available. As the first step to characterizing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(39 citation statements)
references
References 68 publications
(86 reference statements)
0
39
0
Order By: Relevance
“…In all, 47 insertion mutants were detected in 36 distinct Myb genes by screening a total of 73 genes. However, none of the insertions gave rise to morphological phenotypes visible in soil-grown plants [11]. The redundancy of Myb genes may diminish the efficiency of the molecular approach by complementation of function.…”
Section: Introductionmentioning
confidence: 99%
“…In all, 47 insertion mutants were detected in 36 distinct Myb genes by screening a total of 73 genes. However, none of the insertions gave rise to morphological phenotypes visible in soil-grown plants [11]. The redundancy of Myb genes may diminish the efficiency of the molecular approach by complementation of function.…”
Section: Introductionmentioning
confidence: 99%
“…LOC_Os07g12130, as a pms1(t) candidate gene, encodes a Myb-like protein with a DNA binding domain. Myb proteins are the largest superfamily of transcription factors that play a regulating role in the process of development and defense reaction, such as regulation of plant cell shape, growth regulators, and responses to stress (Meissner et al, 1999). A new Myb-like gene (AtMYB103) showed a high level of mRNA expression in the early development of anther tapetum and middle-level performance in Arabidopsis thaliana (Li et al, 1999).…”
Section: Correlation Between Myb-like Protein and Ptgms Genementioning
confidence: 99%
“…In Arabidopsis more than 92 MYB genes have been described [38]. In plants, MYB genes regulate secondary metabolism, cell morphology, and signal transduction in plant growth and pathogen defense [39].…”
Section: Resultsmentioning
confidence: 99%
“…Further research is needed to determine the function of this transcription factor. However, in gene-disruption experiments, Meissner et al [38] found no obvious phenotypes in 32 homozygous insertion lines of 26 genes. Even more intensive greenhouse and plate-based screening failed to find a phenotype for most of these plants, possibly indicating redundancy [38].…”
Section: Resultsmentioning
confidence: 99%